2000
DOI: 10.2118/67608-pa
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Compression Forces on Casing-String Designs and Connectors

Abstract: Summary The effect of downhole axial compression forces on casing string designs and connectors is a major concern to engineers designing high-temperature, high-pressure, extended reach, and horizontal wells. Widespread concern regarding the significance of compression loads on casing string design is relatively recent. For decades engineers were either not aware that high-compression loads may occur or were not concerned about the effect of compression on the casing. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…As such, they developed a semi-analytical model that can be applicable to study various wellhead loading situations that can potentially cause motion in the upward direction. In contrast, Awe et al (2015) and Jellison and Brock (1998) identified connection failure, local buckling and shear failure as the main types of failures on casing strings. Even though both API and ISO have issued recommended practice for connection evaluation procedure (API RP 5C5 and ISO/PAS 12835) left much to be desired for hydraulically fractured wells (Hamilton 2019).…”
Section: Connection Failurementioning
confidence: 93%
“…As such, they developed a semi-analytical model that can be applicable to study various wellhead loading situations that can potentially cause motion in the upward direction. In contrast, Awe et al (2015) and Jellison and Brock (1998) identified connection failure, local buckling and shear failure as the main types of failures on casing strings. Even though both API and ISO have issued recommended practice for connection evaluation procedure (API RP 5C5 and ISO/PAS 12835) left much to be desired for hydraulically fractured wells (Hamilton 2019).…”
Section: Connection Failurementioning
confidence: 93%